Avaliação do comportamento reológico, térmico e mecânico de misturas de PBAT com elevados teores de lignina - Torrezan, Talyta (2019)
The massive accumulation of plastic waste and its environmental impact is in great evidence today. Each year, more than 8 million tons end up in the oceans, so research indicates that there will be more plastics than fishs in mass in the oceans by 2050. Amid this alarming data, environmental pressures for solutions that serve a circular economy have been rising sharply. Among these, it has focused on encouraging the use of biodegradable polymers in agriculture, as this application provides environmentally sustainable cycles, from renewable sources to biodegradation. Given this, the present work aimed to develop a technically, economically and environmentally viable solution for rigid plastic parts focusing on the agricultural segment, where one of the main materials composing this solution was the largest renewable source of aromatics present in nature, also known as lignin. PBAT mixtures with high lignin contents were developed, focusing on bringing scientific and technological basis through rheological, thermal and mechanical evaluations. Such a study was successful in demonstrating the existence of two behavior categories represented by lignin concentration. Up to 20% by mass, they are miscible or partially miscible structured blends, where lignin acts as a lubricant. For contents above 40% of lignin by mass, there are systems composed of partially miscible blends. For this group of higher concentrations, there is possibly the generation of domains, interconnected networks (lignin-lignin and PBAT-lignin), which reduce the ability to dissipate energy viscously, demonstrating a character closer to an elastic solid. Thus, the results obtained here contribute to the structural understanding of such mixtures, allowing the foundation to reach the technical requirements needed in the development of different sustainable solutions to be applied to rigid plastic parts in the agricultural segment, such as seedling tubes, where it would be possible the experience of infinite cycles of lignin generation using one's own for such.